Improved forecasting of cotton canopy temperature for irrigation scheduling - Stephen Rogers; Huidong Jin; Rose Roche; Danielle A. Way (Agricultural and Forest Meteorology, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Is tree planting an effective strategy for climate change mitigation? - Miko U.F. Kirschbaum; Annette L. Cowie; Josep Peñuelas; Pete Smith; Richard T. Conant; Rowan F. Sage; Miguel Brandão; M. Francesca Cotrufo; Yiqi Luo; Danielle A. Way; Sharon A. Robinson (Science of The Total Environment, 2024)

How will increased atmospheric CO2 and climate change-induced wind trends alter the probability of tree failures from wind gusts - Samuel Woolsey; Horia Hangan; Hassan Peerhossaini; Danielle Way (Agricultural and Forest Meteorology, 2023)

Reducing model uncertainty of climate change impacts on high latitude carbon assimilation - Alistair Rogers; Shawn P. Serbin; Danielle A. Way (Global Change Biology, 2022)
The Arctic–Boreal Region (ABR) has a large impact on global vegetation–atmosphere interactions and is experiencing markedly greater warming than the rest of the planet, a trend that is projected to continue with anticipated future emissions of CO 2 . The ABR is a significant source of uncertainty in estimates of carbon uptake in terrestrial biosphere models such that reducing this uncertainty is critical for more accurately estimating global carbon cycling and understanding the response of the region to global change. Process representation and parameterization associated with gross primary productivity (GPP) drives a large amount of this model uncertainty, particularly within the next 50 years, where the response of existing vegetation to climate change will dominate estimates of GPP for the region. Here we review our current understanding and model representation of GPP in northern latitudes, focusing on vegetation composition, phenology, and physiology, and consider how climate change alters these three components. We highlight challenges in the ABR for predicting GPP, but also focus on the unique opportunities for advancing knowledge and model representation, particularly through the combination of remote sensing and traditional boots‐on‐the‐ground science.

Essential outcomes for COP26 - Pete Smith; Linda Beaumont; Carl J. Bernacchi; Maria Byrne; William Cheung; Richard T. Conant; Francesca Cotrufo; Xiaojuan Feng; Ivan Janssens; Hefin Jones; Miko U. F. Kirschbaum; Kazuhiko Kobayashi; et al. (Global Change Biology, 2022)

Limited thermal acclimation of photosynthesis in tropical montane tree species - Mirindi Eric Dusenge; Maria Wittemann; Myriam Mujawamariya; Elisée B. Ntawuhiganayo; Etienne Zibera; Bonaventure Ntirugulirwa; Danielle A. Way; Donat Nsabimana; Johan Uddling; Göran Wallin (Global Change Biology, 2021)
The temperature sensitivity of physiological processes and growth of tropical trees remains a key uncertainty in predicting how tropical forests will adjust to future climates. In particular, our knowledge regarding warming responses of photosynthesis, and its underlying biochemical mechanisms, is very limited. We grew seedlings of two tropical montane rainforest tree species, the early‐successional species Harungana montana and the late‐successional species Syzygium guineense , at three different sites along an elevation gradient, differing by 6.8℃ in daytime ambient air temperature. Their physiological and growth performance was investigated at each site. The optimum temperature of net photosynthesis ( T optA ) did not significantly increase in warm‐grown trees in either species. Similarly, the thermal optima ( T optV and T optJ ) and activation energies ( E aV and E aJ ) of maximum Rubisco carboxylation capacity ( V cmax ) and maximum electron transport rate ( J max ) were largely unaffected by warming. However, V cmax , J max and foliar dark respiration ( R d ) at 25℃ were significantly reduced by warming in both species, and this decline was partly associated with concomitant reduction in total leaf nitrogen content. The ratio of J max / V cmax decreased with increasing leaf temperature for both species, but the ratio at 25℃ was constant across sites. Furthermore, in H . montana , stomatal conductance at 25℃ remained constant across the different temperature treatments, while in S . guineense it increased with warming. Total dry biomass increased with warming in H . montana but remained constant in S . guineense . The biomass allocated to roots, stem and leaves was not affected by warming in H . montana , whereas the biomass allocated to roots significantly increased in S . guineense . Overall, our findings show that in these two tropical montane rainforest tree species, the capacity to acclimate the thermal optimum of photosynthesis is limited while warming‐induced reductions in respiration and photosynthetic capacity rates are tightly coupled and linked to responses of leaf nitrogen.

Warming induces divergent stomatal dynamics in co‐occurring boreal trees - Mirindi E. Dusenge; Eric J. Ward; Jeffrey M. Warren; Joseph R. Stinziano; Stan D. Wullschleger; Paul J. Hanson; Danielle A. Way (Global Change Biology, 2021)
Climate warming will alter photosynthesis and respiration not only via direct temperature effects on leaf biochemistry but also by increasing atmospheric dryness, thereby reducing stomatal conductance and suppressing photosynthesis. Our knowledge on how climate warming affects these processes is mainly derived from seedlings grown under highly controlled conditions. However, little is known regarding temperature responses of trees growing under field settings. We exposed mature tamarack and black spruce trees growing in a peatland ecosystem to whole‐ecosystem warming of up to +9°C above ambient air temperatures in an ongoing long‐term experiment (SPRUCE: Spruce and Peatland Responses Under Changing Environments). Here, we report the responses of leaf gas exchange after the first two years of warming. We show that the two species exhibit divergent stomatal responses to warming and vapor pressure deficit. Warming of up to 9°C increased leaf N in both spruce and tamarack. However, higher leaf N in the warmer plots translate into higher photosynthesis in tamarack but not in spruce, with photosynthesis being more constrained by stomatal limitations in spruce than in tamarack under warm conditions. Surprisingly, dark respiration did not acclimate to warming in spruce, and thermal acclimation of respiration was only seen in tamarack once changes in leaf N were considered. Our results highlight how warming can lead to differing stomatal responses to warming in co‐occurring species, with consequent effects on both vegetation carbon and water dynamics.

Systemic effects of rising atmospheric vapor pressure deficit on plant physiology and productivity - José López; Danielle A. Way; Walid Sadok (Global Change Biology, 2021)
Earth is currently undergoing a global increase in atmospheric vapor pressure deficit (VPD), a trend which is expected to continue as climate warms. This phenomenon has been associated with productivity decreases in ecosystems and yield penalties in crops, with these losses attributed to photosynthetic limitations arising from decreased stomatal conductance. Such VPD increases, however, have occurred over decades, which raises the possibility that stomatal acclimation to VPD plays an important role in determining plant productivity under high VPD. Furthermore, evidence points to more far‐ranging and complex effects of elevated VPD on plant physiology, extending to the anatomical, biochemical, and developmental levels, which could vary substantially across species. Because these complex effects are typically not considered in modeling frameworks, we conducted a quantitative literature review documenting temperature‐independent VPD effects on 112 species and 59 traits and physiological variables, in order to develop an integrated and mechanistic physiological framework. We found that VPD increase reduced yield and primary productivity, an effect that was partially mediated by stomatal acclimation, and also linked with changes in leaf anatomy, nutrient, and hormonal status. The productivity decrease was also associated with negative effects on reproductive development, and changes in architecture and growth rates that could decrease the evaporative surface or minimize embolism risk. Cross‐species quantitative relationships were found between levels of VPD increase and trait responses, and we found differences across plant groups, indicating that future VPD impacts will depend on community assembly and crop functional diversity. Our analysis confirms predictions arising from the hydraulic corollary to Darcy's law, outlines a systemic physiological framework of plant responses to rising VPD, and provides recommendations for future research to better understand and mitigate VPD‐mediated climate change effects on ecosystems and agro‐systems.

Announcing GCB reviews – The past, present and future of global change biology at your fingertips - Danielle A. Way (Global Change Biology, 2021)

Lipidomic Analysis of Postmortem Prefrontal Cortex Phospholipids Reveals Changes in Choline Plasmalogen Containing Docosahexaenoic Acid and Stearic Acid Between Cases With and Without Alzheimer’s Disease - Yurika Otoki; Shunji Kato; Kiyotaka Nakagawa; Danielle J. Harvey; Lee-Way Jin; Britany N. Dugger; Ameer Y. Taha (NeuroMolecular Medicine, 2021)

Contrasting acclimation responses to elevated CO 2 and warming between an evergreen and a deciduous boreal conifer - Mirindi E. Dusenge; Sasha Madhavji; Danielle A. Way (Global Change Biology, 2020)
Rising atmospheric carbon dioxide (CO 2 ) concentrations may warm northern latitudes up to 8°C by the end of the century. Boreal forests play a large role in the global carbon cycle, and the responses of northern trees to climate change will thus impact the trajectory of future CO 2 increases. We grew two North American boreal tree species at a range of future climate conditions to assess how growth and carbon fluxes were altered by high CO 2 and warming. Black spruce ( Picea mariana , an evergreen conifer) and tamarack ( Larix laricina , a deciduous conifer) were grown under ambient (407 ppm) or elevated CO 2 (750 ppm) and either ambient temperatures, a 4°C warming, or an 8°C warming. In both species, the thermal optimum of net photosynthesis ( T optA ) increased and maximum photosynthetic rates declined in warm‐grown seedlings, but the strength of these changes varied between species. Photosynthetic capacity (maximum rates of Rubisco carboxylation, V cmax , and of electron transport, J max ) was reduced in warm‐grown seedlings, correlating with reductions in leaf N and chlorophyll concentrations. Warming increased the activation energy for V cmax and J max ( E aV and E aJ , respectively) and the thermal optimum for J max . In both species, the T optA was positively correlated with both E aV and E aJ , but negatively correlated with the ratio of J max / V cmax . Respiration acclimated to elevated temperatures, but there were no treatment effects on the Q 10 of respiration (the increase in respiration for a 10°C increase in leaf temperature). A warming of 4°C increased biomass in tamarack, while warming reduced biomass in spruce. We show that climate change is likely to negatively affect photosynthesis and growth in black spruce more than in tamarack, and that parameters used to model photosynthesis in dynamic global vegetation models ( E aV and E aJ ) show no response to elevated CO 2 .

Civil disobedience movements such as School Strike for the Climate are raising public awareness of the climate change emergency - Stephen J. Thackeray; Sharon A. Robinson; Pete Smith; Rhea Bruno; Miko U. F. Kirschbaum; Carl Bernacchi; Maria Byrne; William Cheung; M. Francesca Cotrufo; Phillip Gienapp; Sue Hartley; Ivan Janssens; et al. (Global Change Biology, 2020)

Modelled net carbon gain responses to climate change in boreal trees: Impacts of photosynthetic parameter selection and acclimation - Joseph R. Stinziano; William L. Bauerle; Danielle A. Way (Global Change Biology, 2019)
Boreal forests are crucial in regulating global vegetation‐atmosphere feedbacks, but the impact of climate change on boreal tree carbon fluxes is still unclear. Given the sensitivity of global vegetation models to photosynthetic and respiration parameters, we determined how predictions of net carbon gain (C‐gain) respond to variation in these parameters using a stand‐level model (MAESTRA). We also modelled how thermal acclimation of photosynthetic and respiratory temperature sensitivity alters predicted net C‐gain responses to climate change. We modelled net C‐gain of seven common boreal tree species under eight climate scenarios across a latitudinal gradient to capture a range of seasonal temperature conditions. Physiological parameter values were taken from the literature together with different approaches for thermally acclimating photosynthesis and respiration. At high latitudes, net C‐gain was stimulated up to 400% by elevated temperatures and CO 2 in the autumn but suppressed at the lowest latitudes during midsummer under climate scenarios that included warming. Modelled net C‐gain was more sensitive to photosynthetic capacity parameters ( V cmax , J max , Arrhenius temperature response parameters, and the ratio of J max to V cmax ) than stomatal conductance or respiration parameters. The effect of photosynthetic thermal acclimation depended on the temperatures where it was applied: acclimation reduced net C‐gain by 10%–15% within the temperature range where the equations were derived but decreased net C‐gain by 175% at temperatures outside this range. Thermal acclimation of respiration had small, but positive, impacts on net C‐gain. We show that model simulations are highly sensitive to variation in photosynthetic parameters and highlight the need to better understand the mechanisms and drivers underlying this variability (e.g., whether variability is environmentally and/or biologically driven) for further model improvement.

Improving models of photosynthetic thermal acclimation: Which parameters are most important and how many should be modified? - Joseph R. Stinziano; Danielle A. Way; William L. Bauerle (Global Change Biology, 2018)
Photosynthetic temperature acclimation could strongly affect coupled vegetation–atmosphere feedbacks in the global carbon cycle, especially as the climate warms. Thermal acclimation of photosynthesis can be modelled as changes in the parameters describing the direct effect of temperature on photosynthetic capacity (i.e., activation energy, E a ; deactivation energy, H d ; entropy parameter, Δ S ) or the basal value of photosynthetic capacity (i.e., photosynthetic capacity measured at 25°C). However, the impact of acclimating these parameters (individually or in combination) on vegetative carbon gain is relatively unexplored. Here we compare the ability of 66 photosynthetic temperature acclimation scenarios to improve the ability of a spatially explicit canopy carbon flux model, MAESTRA , to predict eddy covariance data from a loblolly pine forest. We show that: (1) incorporating seasonal temperature acclimation of basal photosynthetic capacity improves the model's ability to capture seasonal changes in carbon fluxes and outperforms acclimation of other single factors (i.e., E a or Δ S alone); (2) multifactor scenarios of photosynthetic temperature acclimation provide minimal (if any) improvement in model performance over single factor acclimation scenarios; (3) acclimation of E a should be restricted to the temperature ranges of the data from which the equations are derived; and (4) model performance is strongly affected by the H d parameter. We suggest that a renewed effort be made into understanding whether basal photosynthetic capacity, E a , H d and Δ S co‐acclimate across broad temperature ranges to determine whether and how multifactor thermal acclimation of photosynthesis occurs.

Carbon fluxes acclimate more strongly to elevated growth temperatures than to elevated CO 2 concentrations in a northern conifer - Yulia Kroner; Danielle A. Way (Global Change Biology, 2016)
Increasing temperatures and atmospheric CO 2 concentrations will affect tree carbon fluxes, generating potential feedbacks between forests and the global climate system. We studied how elevated temperatures and CO 2 impacted leaf carbon dynamics in Norway spruce ( Picea abies ), a dominant northern forest species, to improve predictions of future photosynthetic and respiratory fluxes from high‐latitude conifers. Seedlings were grown under ambient ( AC , c . 435 μ mol mol −1 ) or elevated ( EC , 750 μ mol mol −1 ) CO 2 concentrations at ambient, +4 °C, or +8 °C growing temperatures. Photosynthetic rates (A sat ) were high in +4 °C/ EC seedlings and lowest in +8 °C spruce, implying that moderate, but not extreme, climate change may stimulate carbon uptake. A sat , dark respiration (R dark ), and light respiration (R light ) rates acclimated to temperature, but not CO 2 : the thermal optimum of A sat increased, and R dark and R light were suppressed under warming. In all treatments, the Q 10 of R light (the relative increase in respiration for a 10 °C increase in leaf temperature) was 35% higher than the Q 10 of R dark , so the ratio of R light to R dark increased with rising leaf temperature. However, across all treatments and a range of 10–40 °C leaf temperatures, a consistent relationship between R light and R dark was found, which could be used to model R light in future climates. Acclimation reduced daily modeled respiratory losses from warm‐grown seedlings by 22–56%. When R light was modeled as a constant fraction of R dark , modeled daily respiratory losses were 11–65% greater than when using measured values of R light . Our findings highlight the impact of acclimation to future climates on predictions of carbon uptake and losses in northern trees, in particular the need to model daytime respiratory losses from direct measurements of R light or appropriate relationships with R dark .

Thermal acclimation of photosynthesis: on the importance of adjusting our definitions and accounting for thermal acclimation of respiration - Danielle A. Way; Wataru Yamori (Photosynthesis Research, 2014)

Temperature response of photosynthesis in C3, C4, and CAM plants: temperature acclimation and temperature adaptation - Wataru Yamori; Kouki Hikosaka; Danielle A. Way (Photosynthesis Research, 2014)

Enhanced isoprene-related tolerance of heat- and light-stressed photosynthesis at low, but not high, CO2 concentrations - Danielle A. Way; Jörg-Peter Schnitzler; Russell K. Monson; Robert B. Jackson (Oecologia, 2011)

Greater seed production in elevated CO 2 is not accompanied by reduced seed quality in Pinus taeda L. - DANIELLE A. WAY; SHANNON L. LADEAU; HEATHER R. MCCARTHY; JAMES S. CLARK; RAM OREN; ADRIEN C. FINZI; ROBERT B. JACKSON (Global Change Biology, 2010)
For herbaceous species, elevated CO 2 often increases seed production but usually leads to decreased seed quality. However, the effects of increased atmospheric CO 2 on tree fecundity remain uncertain, despite the importance of reproduction to the composition of future forests. We determined how seed quantity and quality differed for pine trees grown for 12 years in ambient and elevated (ambient+200 μL L −1 ) CO 2 , at the Duke Forest free‐air CO 2 enrichment (FACE) site. We also compared annual reproductive effort with yearly measurements of aboveground net primary productivity (ANPP), precipitation (P), potential evapotranspiration (PET) and water availability [precipitation minus potential evapotranspiration (P−PET)] to investigate factors that may drive interannual variation in seed production. The number of mature, viable seeds doubled per unit basal area in high‐CO 2 plots from 1997 to 2008 ( P 2 effect on mean seed mass, viability, or nutrient content. Interannual variation in seed production was positively related to ANPP, with a similar percentage of ANPP diverted to reproduction across years. Seed production was negatively related to PET ( P P P =0.88). This study adds to the few findings that, unlike herbaceous crops, woody plants may benefit from future atmospheric CO 2 by producing larger numbers of seeds without suffering degraded seed quality. Differential reproductive responses between functional groups and species could facilitate woody invasions or lead to changes in forest community composition as CO 2 rises.

Elevated growth temperatures reduce the carbon gain of black spruce [ Picea mariana (Mill.) B.S.P.] - DANIELLE A. WAY; ROWAN F. SAGE (Global Change Biology, 2008)
We explored the effect of high‐growth temperatures on a dominant North American boreal tree, black spruce [ Picea mariana (Mill.) B.S.P.]. In 2004 and 2005, we grew black spruce at either 22 °C/16 °C day/night temperatures [low temperature (LT)] or 30°/24 °C [high temperature (HT)] and determined how temperature affected growth, leaf morphology, photosynthesis, respiration and thermotolerance. HT spruce were 20% shorter, 58% lighter, and had a 58% lower root : shoot ratio than LT trees. Mortality was negligible in the LT treatment, but up to 14% of HT seedlings died by the end of the growing season. HT seedlings had a higher photosynthetic temperature optimum, but net photosynthesis at growth temperatures was 19–35% lower in HT than LT trees. HT seedlings had both a lower apparent maximum ribulose‐1,5‐bisphosphate carboxylation capacity ( V cmax ) and a lower apparent maximum electron transport rate ( J max ) than LT trees, indicating reduced allocation to photosynthetic components. Consistently, HT needles had 26% lower leaf nitrogen content than LT needles. At each measurement temperature, HT seedlings had 20–25% lower respiration rates than LT trees; however, this did not compensate for reduced photosynthetic rates at growth temperature, leading to a greater ratio of dark respiration to net carbon dioxide assimilation rate in HT trees. HT needles had 16% lower concentrations of soluble sugars than LT needles, but similar starch content. Growth at high temperatures increased the thermotolerance of black spruce. HT trees showed less PSII inhibition than LT seedlings and no increase in electrolyte leakage when briefly exposed to 40–57 °C. While trees that develop at high temperatures have enhanced tolerance for brief, extreme heat events, the reduction in root allocation indicates that seedlings will be more susceptible to episodic soil drying and less competitive for belowground resources in future climates of the boreal region.

The effect of carbon and nutrient loading during nursery culture on the growth of black spruce seedlings: a six-year field study - Danielle A. Way; Seth D. Seegobin; Rowan F. Sage (New Forests, 2007)

Estimation of the whole‐plant CO 2 compensation point of tobacco ( Nicotiana tabacum L.) - Catherine D. Campbell; Rowan F. Sage; Ferit Kocacinar; Danielle A. Way (Global Change Biology, 2005)
The whole‐plant CO 2 compensation point (Γ plant ) is the minimum atmospheric CO 2 level required for sustained growth. The minimum CO 2 requirement for growth is critical to understanding biosphere feedbacks on the carbon cycle during low CO 2 episodes; however, actual values of Γ plant remain difficult to calculate. Here, we have estimated Γ plant in tobacco by measuring the relative leaf expansion rate at several low levels of atmospheric CO 2 , and then extrapolating the leaf growth vs. CO 2 response to estimate CO 2 levels where no growth occurs. Plants were grown under three temperature treatments, 19/15, 25/20 and 30/25°C day/night, and at CO 2 levels of 100, 150, 190 and 270 μmol CO 2 mol −1 air. Biomass declined with growth CO 2 such that Γ plant was estimated to be approximately 65 μmol mol −1 for plants grown at 19/15 and 30/25°C. In the first 19 days after germination, plants grown at 100 μmol mol −1 had low growth rates, such that most remained as tiny seedlings (canopy size 2 ). Most seedlings grown at 150 μmol mol −1 and 30/25°C also failed to grow beyond the small seedling size by day 19. Plants in all other treatments grew beyond the small seedling size within 3 weeks of planting. Given sufficient time (16 weeks after planting) plants at 100 μmol mol −1 eventually reached a robust size and produced an abundance of viable seed. Photosynthetic acclimation did not increase Rubisco content at low CO 2 . Instead, Rubisco levels were unchanged except at the 100 and 150 μmol mol −1 where they declined. Chlorophyll content and leaf weight per area declined in the same proportion as Rubisco, indicating that leaves became less expensive to produce. From these results, we conclude that the effects of very low CO 2 are most severe during seedling establishment, in large part because CO 2 deficiency slows the emergence and expansion of new leaves. Once sufficient leaf area is produced, plants enter the exponential growth phase and acquire sufficient carbon to complete their life cycle, even under warm conditions (30/25°C) and CO 2 levels as low as 100 μmol mol −1 .